2018
DOI: 10.1111/pce.13389
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in tree performance during hotter droughts are mitigated by shifts in nitrogen cycling

Abstract: Climate warming should result in hotter droughts of unprecedented severity in this century. Such droughts have been linked with massive tree mortality, and data suggest that warming interacts with drought to aggravate plant performance. Yet how forests will respond to hotter droughts remains unclear, as does the suite of mechanisms trees use to deal with hot droughts. We used an ecosystem-scale manipulation of precipitation and temperature on piñon pine (Pinus edulis) and juniper (Juniperus monosperma) trees t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
(111 reference statements)
0
17
1
Order By: Relevance
“…In conclusion, lowered foliar macro‐ and micronutrient content under simulated climate change was linked to severely impaired photosynthetic performance and water use efficiency, which led to large decreases in productivity and nutrient pool size in dryland vegetation. In contrast to other dryland studies (Grossiord, Sevanto, Borrego, et al, , Grossiord et al ), we found that warming had a stronger detrimental impact on plant physiological performance and growth than rainfall reduction, and this impact was primarily driven (rather than mitigated) by shifts in foliar elemental composition that increased non‐stomatal constraints on photosynthesis. The large warming‐induced reduction in leaf nutrient contents encountered in this study, and its negative impact on A and WUEi, would be expected to offset any increases in WUE and productivity derived from atmospheric CO 2 elevation during coming decades (Dijkstra et al, ; Morgan et al, ; Norby, Warren, Iversen, Medlyn, & McMurtrie, ), thereby augmenting vegetation vulnerability to drought stress in a warmer and drier climate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In conclusion, lowered foliar macro‐ and micronutrient content under simulated climate change was linked to severely impaired photosynthetic performance and water use efficiency, which led to large decreases in productivity and nutrient pool size in dryland vegetation. In contrast to other dryland studies (Grossiord, Sevanto, Borrego, et al, , Grossiord et al ), we found that warming had a stronger detrimental impact on plant physiological performance and growth than rainfall reduction, and this impact was primarily driven (rather than mitigated) by shifts in foliar elemental composition that increased non‐stomatal constraints on photosynthesis. The large warming‐induced reduction in leaf nutrient contents encountered in this study, and its negative impact on A and WUEi, would be expected to offset any increases in WUE and productivity derived from atmospheric CO 2 elevation during coming decades (Dijkstra et al, ; Morgan et al, ; Norby, Warren, Iversen, Medlyn, & McMurtrie, ), thereby augmenting vegetation vulnerability to drought stress in a warmer and drier climate.…”
Section: Discussioncontrasting
confidence: 99%
“…There is increasing awareness that progressive atmospheric CO 2 elevation (eCO 2 ) with anthropogenic global change threatens plant nutrient status and nutritional quality (Briat, Dubos, & Gaymard, ; Elser, Fagan, Kerkhoff, Swenson, & Enquist, ; Loladze, ), given that eCO 2 decreases leaf nutrient concentrations (6.5%–10%) through carbon dilution effects and reductions in plant transpiration (Loladze, ; Sardans, Rivas‐Ubach, & Peñuelas, ). However, the potential negative impacts of climate aridification on dryland plant nutrition remain understudied and are not well understood (Grossiord et al, ; Sardans et al, , ; Sardans & Peñuelas, ; Yuan & Chen, ). In particular, the influence of climate warming and drying on the foliar concentrations of essential plant micronutrients such as Fe, Cu and Zn in dryland vegetation has received limited research attention despite their key roles in photosynthesis, metabolism and growth (Briat et al, ; Marschner, ; Salazar‐Tortosa et al, ; Tian et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We also show that substantial mortality has already occurred in response to recent, ambient drought conditions: native grass species were particularly sensitive to both ambient and long-term experimental drought, which has potential consequences for shifting ecosystem function and carbon balance in this water-limited system (Gitlin et al, 2006;Scott, Biederman, Hamerlynck, & Barron-Gafford, 2015). Additionally, studies on the Colorado Plateau should examine the potential interactive effects of drought and warmer temperatures that have been shown in some systems to significantly affect mortality and system response (Adams et al, 2009;Breshears et al, 2005;Grossiord et al, 2018). Future studies would benefit from focusing on the interactive role abiotic and biotic factors play in determining plant population responses to drought-induced mortality.…”
Section: Speciesmentioning
confidence: 79%
“…Studies are also needed to uncover the role of ecological memory of past stressors in determining current and future responses (Ogle et al, 2015). Additionally, studies on the Colorado Plateau should examine the potential interactive effects of drought and warmer temperatures that have been shown in some systems to significantly affect mortality and system response (Adams et al, 2009;Breshears et al, 2005;Grossiord et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation